2018
DOI: 10.1016/j.exger.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Age-related arterial immune cell infiltration in mice is attenuated by caloric restriction or voluntary exercise

Abstract: Age-related arterial inflammation is associated with dysfunction of the arteries and increased risk for cardiovascular disease. To determine if aging increases arterial immune cell infiltration as well as the populations of immune cells principally involved, we tested the hypothesis that large elastic and resistance arteries in old mice would exhibit increased immune cell infiltration compared to young controls. Additionally, we hypothesized that vasoprotective lifestyle interventions such as lifelong caloric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…We have previously found that lifelong CR prevents age-related arterial dysfunction [20, 22] and accumulation of T cells in both aorta and the mesenteric vasculature [35]. In the present investigation, we found that age-related increases CXCL10, which recruits T cells, was prevented by CR.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We have previously found that lifelong CR prevents age-related arterial dysfunction [20, 22] and accumulation of T cells in both aorta and the mesenteric vasculature [35]. In the present investigation, we found that age-related increases CXCL10, which recruits T cells, was prevented by CR.…”
Section: Discussionsupporting
confidence: 68%
“…We also found that treatment with Rap lowered MCSF, which recruits and serves as a growth factor for macrophages. Consistent with this observation, aortic perivascular macrophages increase with age [10, 35], and Rap treatment improves arterial function in old mice [21]. The finding that some of the lifespan extending interventions can prevent age-related increases in aortic chemokines that mediate differentiation and recruitment of inflammatory cells represents a potential mechanism by which these interventions might preserve arterial health.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, in vitro monocyte adhesion is blunted in the presence of serum from old caloric‐restricted rats when compared with serum from old rats fed ad libitum (Csiszar et al., ). Caloric restriction also improves PWV and reverses the age‐related increase of MMP9 in mouse large elastic arteries (Donato et al., ), in addition to normalizing age‐related infiltration of aortic T cells, B cells and macrophages (Figure ) and aortic production of the T‐cell‐recruiting chemokine, CXCL10 (Trott et al., , ). Similar effects of caloric restriction on immune cell infiltration was observed in the mesenteric vasculature (Figure ; Trott et al., ).…”
Section: Interventions To Ameliorate Age‐related Inflammation and Artmentioning
confidence: 99%
“…Human, mouse Leucocyte recruitment to artery; promotes large artery stiffening (Donato et al, 2008;Wang et al, 2007Wang et al, , 2011 CC motif chemokine ligand 5; otherwise known as RANTES (Trott et al, 2018) T cells N/A Circulation, perivascular adipose…”
Section: Tgf-whole Artery Mousementioning
confidence: 99%